Modulation of Fear and Arousal Behavior by Serotonin Transporter (5-HTT) Genotypes in Newly Hatched Chickens - Phi Van, Valerie D.; Krause, E. Tobias; Phi-Van, Loc (Frontiers in Behavioral Neuroscience, 2018)
The serotonin transporter (5-HTT) plays a key role in regulating serotonergic transmission via removal of serotonin (5-HT) from synaptic clefts. Alterations in 5-HTT expression and 5-HT transmission have been shown to cause changes to adult behavior including fear. The objective of the present study was to investigate the 5-HTT role in fear in birds at the very early stages of post-hatching life. Using an avoidance test with an elevated balance beam, which was based on depth perception and the respective fear of heights, we assessed fear-related avoidance behaviors of newly hatched chicks of the three functional 5-HTT genotypes W/W, W/D and D/D. Newly hatched chicks of the genotype D/D, which was linked to high 5-HTT expression, showed less intensive avoidance responses as measured by decreased latency to jump than W/W and W/D chicks. Further, significantly fewer D/D hens than W/W hens showed fear-like behavior that resembled a freezing response. Furthermore, in an arousal test the arousal reaction of the chicks in response to an acute short-term visual social deprivation in the home compartment was assessed 5 weeks after hatching, which also revealed that D/D chicks exhibited decreased arousal reaction, compared to W/W chicks. Thus, the results indicate that fear responses differ in D/D chicks in the early post-hatching periods, possibly due to the different expression of 5-HTT respectively 5-HT levels in this strain.